A Portrait of Palestinians in Mahmoud Darwish’s Poem ‘Qasidatu Al-Ardi’: New Historicism Analysis - Qowlits Tsabita, Qonita Qorrie Aini; Arief Rahman Hakim (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
This study aims to elucidate the meaning of the poem